Relational power is the new currency of hybrid work in the new world of work, managers cannot rely solely on traditional hierarchical power structures - Soga, Lebene; Bolade-Ogunfodun, Yemisi; Islam, Nazrul; Amankwah-Amoah, Joseph (MIT Sloan Management Review, 2022)
The growing use of text-based messaging platforms such as Slack and Huddle means that many manager-employee interactions are shifting to these virtual environments as well. When a research team studied text platform interactions to examine the nature of team relationships in a hybrid work setting, they found that managers must incorporate relational power into their leadership approach rather than relying solely on hierarchical position to sustain manager-employee relationships in virtual environments.
"Reprint 64110."
Keywords: Virtual work teams -- Management; Équipes virtuelles; Gestion; Virtual work teams; Management